Economic Impacts of Solar Energy Systems on Regional Development in Africa - Rao, P. Nageswara; Bal, Yakubu Barau; Nazif, D. M.; Gamawa, Mansur Aliyu; Oko, Idiege Augustine; Ikani, Agabi Peter (Darul Yasin Al Sys, 2025)
This study addresses the need for space-efficient, cost-effective residential renewable energy solutions in Nigeria by introducing and evaluating a 5 kW solar tree system tailored to Bauchi State’s solar conditions. The research objective is to determine whether the proposed system can reliably meet a daily energy demand of 30,000 Wh while delivering high performance, durability, and economic benefits. Methodologically, the system is designed with photovoltaic modules, a charge controller, a battery bank, an inverter, and a steel support structure sized for the region’s irradiance; performance, cost savings, and structural integrity are assessed using efficiency, annual bill reduction, and a calculated safety factor. Key findings show that the system achieves over 86% efficiency, saves US1,415 annually on electricity bills, and attains a safety factor of 2.85, indicating robustness against wind and environmental loads; the configuration fulfills the targeted daily energy requirement. The study concludes that the solar tree provides a viable, space-efficient residential solution that reduces reliance on fossil fuels. The contribution and implication are a practically implementable design that can support household-level energy transition efforts and inform wider deployment of residential solar technologies in Nigeria.